PERSEPSI MAHASISWA JURUSAN TEKNIK SIPIL FT-UNP TENTANG PELAKSANAAN PLI PADA DUNIA JASA KONSTRUKSI - 488-494 , Faire Priandika (Universitas Negeri Padang, 2014)
ABSTRACK This study is a descriptive study that aims to describe and interpret the data obtained on an overview of the perceptions of students of Department of Civil Engineering FT-UNP on implementation experience in the world of construction services indrustri the period July-December, 2013. The population of this research is the students of Department of Civil Engineering who has carried out the PLI in the period July-December 2013, the total sample was taken using sampling with a sample of 69 students. The results showed perceptions of students majoring in civil engineering FT-UNP on the implementation of industry experience in the world of construction services in the following activities: observation with the degree of achievement of 68.09%, with the degree of achievement of planning activities and implementation activities 67.34% with 67.86% degree attainment. Based on the degree of achievement, can all be classified simply. Overall perception of students of Department of Civil Engineering FT-UNP on the implementation of industry experience in the construction world degrees 67.75% and include enough categories. Keywords: perception, PLI Implementation, World Construction Services.